GAYA KEPEMIMPINAN DAN MOTIVASI BERPENGARUH TERHADAP KINERJA KARYAWAN PT CITRA WASPPHUTOWA - Didik Pebriyanto; Fajar Cahyo Utomo (Program Studi Magister Manajemen Fakultas Ekonomi Universitas Krisnadwipayana, 2022)
Leadership Style and Motivation Affect Employee Performance PT. Citra Waspphutowa. To determine leadership style and motivation affect employee performance PT. Citra Waspphutowa. This research is included in the category of causal associative research using a quantitative approach. The research population was 123 people, using the Slovin formula, the sample in this study was 55 employees of PT. Citra Waspphutowa. The research method using simultaneous and partially linear regression analysis. The results showed that simultaneous or partially leadership style and motivation had a positive and significant effect on employee performance PT. Citra Waspphutowa.